UJI KUAT TEKAN DAN KEAUSAN BAHAN KAMPAS REM DARI KOMPOSISI TEMPURUNG KEMIRI DAN SERAT BAMBU - Athif, Muh Asyraf (JFT: Jurnal Fisika dan Terapannya, 2018)
This research aims to find out the best composition of brake lining materials from the shell of candlelnut and bamboo fiber through hardness testing and wear and tear of brake lining materials. The method used is direct emphasis using the Universal Testing Machine and Oghosi tools using the High Speed Universal Wear Testing Machine (Type OAT-U) Oghosi tool. Brake lining materials consist of shell powder of candlenut and bamboo fiber and then added aluminum powder and polyester resin with percent of specific composition for each sample. The results of this study were the five samples having lower wear value than the market but only the sample 4 with the composition of 15% of the shell powder of candlenut, 30% bamboo fiber, 15% aluminum powder and 40% polyester resin recommended as alternative material of brake lining because of its hardness close to the hardness of the material of brake lining of the market is 13.5 BHN and its wear is 2,96 x 10-6 mm2 / kg.Key Words: Strong Test of Pressure, Wear of Brush, Bamboo Fiber, Shell Powder of Candlenut, Aluminium Powder, and Resin